Faktor Kegagalan Pengembangan Media Pembelajaran Guru Sosiologi di SMAN 15 Padang - Sari, Pustika; Gautama, Mohammad Isa (Naradidik: Journal of Education and Pedagogy, 2022)
The failure factor in developing learning media for Sociology Teachers at SMA N 15 Padang, in terms of Affective Sociology Teachers at SMAN 15 Padang received learning media in the process of developing learning media. In terms of Cognitive Sociology Teachers at SMAN 15 Padang usually invite students to discuss and ask questions related to the learning material delivered through learning media whether this media is suitable for use or needs to be re-evaluated. Likewise Psychomotor, Sociology Teacher of SMAN 15 Padang conveyed this learning media through Google Classroom and also Google Meet to make it easier for teachers to deliver material. Even so, this Sociology teacher at SMAN 15 Padang still does not apply learning media, this can be seen when getting secondary data where the learning media used are only PPT and videos taken from Youtube. From the results of research at SMAN 15 Padang Sociology teachers must be more active in studying learning media from various sources.